Assessment of the health status and health service perceptions of international migrants coming to Guangzhou, China, from high-, middle- and low-income countries - Remina Maimaitijiang; Qiangsheng He; Yanan Wu; Jennifer Z. H. Bouey; Ahoua Koné; Yucheng Liang; Chun Hao; Jiong Tu; Jing Gu; Yuantao Hao (BMC, 2019)
Abstract Background China, which used to be an export country for migrants, has become a new destination for international migrants due to its rapid economic growth. However, little empirical data is available on the health status of and health service access barriers faced by these international migrants. Methods Foreigners who visited the Guangzhou Municipal Exit-Entry Administration Office to extend their visas were invited to participate in the study. Quantitative data were collected using electronic questionnaire in 13 languages. The participants were characterised by the income level of their country of origin (high-, middle- and low-income countries (HICs, MICs and LICs, respectively)), and the key factors associated with their health status, medical insurance coverage and perceptions of health services in China were examined. Results Overall, 1146 participants from 119 countries participated in the study, 57.1, 25.1 and 17.8% of whom were from MICs, HICs and LICs, respectively. Over one fifth of the participants experienced health problems while staying in China, and about half had no health insurance. Although the participants from HICs were more likely than those from MICs and LICs to have medical insurance, they were also more likely to have health problems. Furthermore, 43.0, 45.0 and 12.0% of the participants thought that the health services in China were good, fair and poor, respectively. Among the participants, those from HICs were less likely to have positive feedback. Conclusions Our study is the first to report a quantitative survey of the health status, health insurance coverage, and health service perceptions of a diverse and surging population of international migrants in China. The findings call for more in-depth studies on the challenges presented by the increasing global migration to the health system.